Fate of antimony contamination generated by road traffic – A focus on Sb geochemistry and speciation in stormwater ponds. (February 2023) - Philippe, M.; Le Pape, P.; Resongles, E.; Landrot, G.; Freydier, R.; Bordier, L.; Baptiste, B.; Delbes, L.; Baya, C.; Casiot, C.; Ayrault, S.
Abstract: Although antimony (Sb) contamination has been documented in urban areas, knowledge gaps remain concerning the contributions of the different sources to the Sb urban biogeochemical cycle, including non-exhaust road traffic emissions, urban materials leaching/erosion and waste incineration. Additionally, details are lacking about Sb chemical forms involved in urban soils, sediments and water bodies. Here, with the aim to document the fate of metallic contaminants emitted through non-exhaust traffic emissions in urban aquatic systems, we studied trace element contamination, with a particular focus on Sb geochemistry, in three highway stormwater pond systems, standing as models of surface environments receiving road-water runoff. In all systems, differentiated on the basis of lead isotopic signatures, Sb shows the higher enrichment factor with respect to the geochemical background, up to 130, compared to other traffic-related inorganic contaminants (Co, Cr, Ni, Cu, Zn, Cd, Pb). Measurements of Sb isotopic composition (δ 123 Sb) performed on solid samples, including air-exposed dusts and underwater sediments, show an average signature of 0.07 ± 0.05‰ (n = 25, all sites), close to the δ 123 Sb value measured previously in certified reference material of road dust (BCR 723, δ 123 Sb = 0.03 ± 0.05‰). Moreover, a fractionation of Sb isotopes is observed between solid and dissolved phases in one sample, which might result from Sb (bio)reduction and/or adsorption processes. SEM-EDXS investigations show the presence of discrete submicrometric particles concentrating Sb in all the systems, interpreted as friction residues of Sb-containing brake pads. Sb solid speciation determined by linear combination fitting of X-Ray Absorption Near Edge Structure (XANES) spectra at the Sb K -edge shows an important spatial variability in the ponds, with Sb chemical forms likely driven by local redox conditions: "dry" samples exposed to air exhibited contributions from Sb(V)–O (52% to 100%) and Sb(III)–O (<10% to 48%) species whereas only underwater samples, representative of suboxic/anoxic conditions, showed an additional contribution from Sb(III)–S (41% to 80%) species. Altogether, these results confirm the traffic emission as a specific source of Sb emission in surface environments. The spatial variations of Sb speciation observed along the road-to-pond continuum likely reflect a high geochemical reactivity, which could have important implications on Sb transfer properties in (sub)surface hydrosystems. Graphical abstract: Image 1 Highlights: Highway stormwater ponds concentrate Sb contamination from road runoff. Sb isotopic composition of stormwater pond sediments is close to that of road dusts. Sb(V)–O, Sb(III)–O, and Sb(III)–S species occur in the road-to-pond continuum. Sb(III)–S species are observed as a specific signature of underwater reduced samples. Sb speciation changes along the waterway show the high geochemical reactivity of Sb.